Pyrolytic and kinetic characteristics of the thermal decomposition of Perilla frutescens polysaccharide. - Quancheng Zhou; Hongmei Zhang; Guihua Sheng (PLoS ONE, 2012)
The thermal decomposition of Perilla frutescens polysaccharide was examined by thermogravimetry, differential thermogravimetry, and differential thermal analysis. The results showed that the mass loss of the substance proceeded in three steps. The first stage can be attributed to the expulsion of the water from ambient temperature to 182°C. The second stage corresponded to devolatilization from 182°C to 439°C. The residue slowly degraded in the third stage. The weight loss in air is faster than that in nitrogen, because the oxygen in air accelerated the pyrolytic reaction speed reaction. The heating rate significantly affected the pyrolysis of the sample. Similar activation energies of the degradation process (210-211 kJ mol⁻¹) were obtained by the FWO, KAS, and Popescu techniques. According to Popescu mechanism functions, the possible kinetic model was estimated to be Avrami-Erofeev 20 g(α) = [-ln(1-α)]⁴.